1812 La. Acts 172, 174, § 1 - (:unkn) unknown (General Publisher, 1813)
Prohibited the carrying of any concealed weapon, including a dirk, dagger, knife, pistol, or any other deadly weapon.
--
Keywords: CARRY - CONCEALED